P-268 Impaired Dilation of Mesenteric Arteries from IL-10-deficient Mice with H. Hepaticus-induced Colitis to Substance P but Not to CGRP. (February 2017) - Boerman, Erika; Hart, Marcia; Franklin, Craig; Segal, Steven
Abstract : Background: Mesenteric arteries are innervated by perivascular sympathetic and sensory nerves that are activated to produce vasoconstriction and vasodilation, respectively, thereby regulating intestinal blood flow. With inflammatory bowel disease, increased serum levels of the anti-inflammatory sensory neurotransmitter calcitonin gene-related peptide (CGRP) are linked to decreased disease severity, while increased proinflammatory substance P (SP) correlates to increased severity. However, the effect of CGRP and SP on the intestinal vascular supply in IBD has not been addressed. We tested the hypothesis that sensory neurotransmitter-mediated dilations are impaired in IBD. Methods: Male and female B6.129P2-IL10 tm * Cgn /J (IL-10 knockout) mice bred in-house were inoculated with H. hepaticus by gastric gavage 2 and 4 days after weaning and allowed to develop IBD for 90 days prior to study. Non-inoculated littermates do not develop colitis and served as controls (n = 6–8 per group). Second-order mesenteric arteries were isolated, cannulated onto glass micropipettes, pressurized to 100 cm H2 O and warmed to 37°C with physiological salt solution in the presence and absence of norepinephrine (NE), CGRP or SP, with inner diameters recorded continuously. Additional arteries were fixed and fluorescently labelled for perivascular nerves using the pan-neuronal marker PGP9.5. Sensory nerves were labelled using both anti-SP and anti-CGRP antibodies. Results: Increasing concentrations of NE (10–9 to 10-5M) produced similar constrictions control and IBD arteries (LogEC50 = −6.6 ± 0.06 and −6.9 ± 0.05), indicating preservation of sympathetic vasoconstrictor function with IBD. To study vasodilation by sensory neurotransmitters, arteries were preconstricted with 10-6M NE then exposed to increasing concentrations of CGRP or SP (10-10 to 10-6M). CGRP had similar effects in control and IBD arteries, with LogEC50 s of −8.6 ± 0.2 and −8.2 ± 0.4 and peak dilations of 74 ± 5% and 61 ± 10% of maximum dilation (measured in the presence of 10-5M sodium nitroprusside). In contrast, dilation to SP effects was with IBD. Thus, while LogEC50 values were similar between control and IBD arteries (−8.4 ± 0.2 and −8.6 ± 0.5, respectively), IBD was associated with ∼50% decrease in peak SP dilations (control, 51 ± 5%; IBD, 23 ± 5% of maximum dilation; P < 0.05). Imaging revealed robust immunofluorescence of perivascular nerves for PGP9.5 and CGRP, while that for SP was much lower from both control and IBD mice. Conclusions: The decrease in SP but not CGRP vasodilator efficacy despite similar immunolabeling for respective neurotransmitters between control and IBD mice suggests impairment in downstream receptor signalling for SP rather than decreased presence of perivascular sensory nerves. The specific decline in SP-mediated dilation points to this neurotransmitter as a potential marker of vascular impairment with IBD and may serve as a target for clinical therapies.